Calibration and validation of a comprehensive kinetic model of coal conversion in inert, air and oxy-fuel conditions using data from multiple test rigs. (15th April 2021) - Debiagi, P.; Ontyd, C.; Pielsticker, S.; Schiemann, M.; Faravelli, T.; Kneer, R.; Hasse, C.; Scherer, V.
Abstract: This work presents detailed information on pyrolysis and char oxidation for a high-volatile Colombian bituminous coal. The investigation includes experiments at low and high particle heating rates, performed in a thermogravimetric analyzer (TGA), a drop-tube reactor (DTR), a flat-flame burner (FFB) and a fluidized-bed reactor (FBR). The TGA and DTR data were used when developing and calibrating the kinetic model for the conversion of coal in air and oxy-fuel atmospheres, while the FFB and FBR data were used to validate the resulting mechanism. The proposed model is an updated version of the CRECK-S-C model from the Politecnico di Milano (PoliMi), consisting of a fuel characterization step, coupled with a multi-step kinetic mechanism based on reference coals. Both the devolatilization and heterogeneous char reactions are accounted for and interconnected seamlessly. Key reactions were introduced and the existing reactions were calibrated to account for the particularities of this fuel and the effects of the abundant CO2 concentration in the reactors. The importance of successive gas-phase reactions was observed and a gas-phase kinetic model was coupled to properly simulate such conditions. The resulting model is applied to simulate and systematically evaluate the experimental findings, highlighting the model's features and limitations.